Bordering and orientation on the cusp of adulthood: 'Scandinavian Afghans' in France. - Lønning, Moa Nyamwathi (Journal of Ethnic & Migration Studies, 2025)
This article engages with the concepts of 'bordering' and 'orientation' to explore experiences of becoming adult under conditions of protracted uncertainty and temporariness. As an analytical framework, these concepts intertwine with space, time and violence, while also accounting for how the structural and subjective shape both inner and outer worlds. The article is based on longitudinal ethnographic fieldwork among young Afghan men who have sought refuge in France after being refused asylum in Sweden and Norway. It considers the bordering effects of legal adulthood (i.e. turning 18) and how finding the way in various contexts of being settled and unsettled redefines what it means to become an adult. The young men's experiences were shaped by their orientation in relation to numerous bordering processes as well as self-making and life-building activities. Moreover, they were deeply affected by the varying ways in which European countries assess Afghan asylum seekers' protection needs.